Der Einsatz von Sprühdüsen zur Reduzierung diffuser Staubemissionen. Issue 3 (30th July 2012) - Klenk, Ulrich; Parey, Matthias
<x xml:space="preserve">Abstract</x> Spray nozzles have been used for a long time for the purpose of reducing dust emissions in exhaust gas streams. Therefore gas scrubbers are used to generate a defined water spray in a defined gas flow to reduce particle concentration in the most effective way by low energy consumption. Droplet size, pressure and water flow rate are adaptable to the exhaust gas flow's properties. In case of using spray nozzles to reduce fugitive dust emissions, e.g. in bulk material handling, the determining factors for emission reduction effectiveness, in contrast to the defined gas flow, vary. A variety of different spraying systems made it necessary to make a selection for different fields of application in relation to their dust‐reducing effects when applying in the bulk handling.